Caper (Capparis spinosa L.): An Updated Review on Its Phytochemistry, Nutritional Value, Traditional Uses, and Therapeutic Potential - Hassan Annaz; Yaya Sane; Gabin Thierry M. Bitchagno; Widad Ben Bakrim; Widad Ben Bakrim; Badreddine Drissi; Ismail Mahdi; Mustapha El Bouhssini; Mansour Sobeh (Frontiers Media S.A., 2022)
Caper (Capparis spinosa L.) is a perennial shrub of the family Capparaceae, endemic to circum-Mediterranean countries. Caper carries a renowned nutritional value, especially in terms of vitamins and antioxidants related to the occurrence of flavonoids, alkaloids, and glucosinolates as main secondary metabolites. Caper extracts have also shown to display antibacterial, antifungal, analgesic, antitumor, hepatoprotective, antioxidant, anti-inflammatory, and neuroprotective effects which correlate the uses of the plant in folk medicine against both metabolic and infectious diseases. The present review aims to provide exhaustive phytochemistry and pharmacological properties survey on Caper constituents. Attention has also been given to the nutritional values and traditional uses of main organs to pinpoint research gaps for future investigations on the plant.